Calibration of Mehlich-3 with Bray P1 and Ammonium Acetate in the Tri-State Region of Ohio, Indiana and Michigan. Issue 1 (2nd January 2020) - Culman, Steve W.; Mann, Meredith; Sharma, Stuti; Saeed, Muhammad Tariq; Fulford, Anthony M.; Lindsey, Laura E.; Brooker, Aaron; Dayton, Elizabeth; Warden, Randall; Joern, Brad
ABSTRACT: Field crop fertilizer recommendations for Ohio, Indiana and Michigan are currently based on the Bray P1 extractant for phosphorus (P) and the ammonium acetate extractant (AA) for base cations. The fertilizer recommendations in this Tri-State region are currently being revised and will use the Mehlich-3 soil test extractant as the new basis for P and potassium (K) fertilizer recommendations. The goal of this study was to document the relationships between Mehlich-3, Bray P1, and AA soil test extractants and to provide a comprehensive review of these relationships published in the literature. Soil samples (n = 2, 659) were collected across Ohio and Indiana from a diverse range of fields and analyzed for Mehlich-3, Bray P1 and AA extractable nutrients for P, K, calcium (Ca), and magnesium (Mg). Mehlich-3 P values were highly related to, but 35% greater than Bray P1 values. Mehlich-3 values were highly related to AA values, but 14% greater than AA-K, 13% greater than AA-Ca and 20% greater than AA-Mg. Our results are largely consistent with a comprehensively compiled literature review that indicates Mehlich-3 is an efficient and suitable soil test extractant for assessing extractable nutrient levels in the Tri-State region of Ohio, Indiana and Michigan.